Performance Evaluation of an Indigenous Metallic Treadle Pump - Sarkar, Amaresh; Jha, Madan K (Journal of Agricultural Engineering, 2010)
Treadle pumps are the most suitable and economical option to supply water for drinking and small-scale irrigation in developing countries. The performance evaluation of a treadle pump is usually done only by measuring discharge. Although few studies have considered operating forces and efficiency of the pump, the details about operating force measurement, input power, output power, mechanical efficiency of the pump and mechanical advantage of the paddles are absent. A scientific methodology is demonstrated for the performance evaluation of a commonly used metallic treadle pump manufactured in India, and to present pump performance data for benefit of the users. The analysis of the experimental data indicated that the metallic treadle pump was able to lift water up to 5 m static suction head. The maximum overall efficiency of the treadle pump was found to be 32.6% at a static suction head of 3.5 m. However, the volumetric efficiency of the pump ranged from 92.9 to 66.7% at static suction heads of 1 to 5 m.